Local Cultural Approach in Navigating Family Conflict: Understanding Cultural Strategies for Human Well-Being - ., Mujiyono; Wahid, Abd. Hamid; Pabbajah, Mustaqim; ., Asriani; Yusuf, Mirna; Fauziah, Eva (Journal of Ecohumanism, 2024)
Objective: This study explores the complexities of family conflict within a local cultural framework, focusing on its impacts on physical and mental well-being through mapping its intensity, root causes, and long-term consequences. The study aims to understand how unresolved interpersonal tensions can negatively impact emotional and social health, ultimately affecting harmony and balance within local communities. The approach uses a theoretical framework that underscores the importance of culture-based communication, negotiation skills that respect local norms, and appreciation for diverse perspectives as steps to reduce conflict and promote mental health. This research contextualizes conflict within various local cultural settings, specifically within families influenced by communal and intergenerational values. Through in-depth analysis of the family as the unit of study, variables such as communication and social relationships are examined with an emphasis on unique socio-cultural dynamics. The findings highlight the negative impact of unresolved family conflict on emotional well-being and the stability of social relationships within the family unit. Conflict can disrupt interpersonal dynamics, creating long-term disharmony that undermines family cohesion. These adverse effects underscore the need for systematic, ongoing interventions to support mental health and collective well-being. This study emphasizes the importance of addressing family conflict as a critical component in achieving the Sustainable Development Goal (SDG) of Good Health and Well-being. Interventions that adopt a local cultural approach—such as effective communication strategies and conflict resolution skills rooted in communal norms—are essential for fostering healthier and more harmonious family environments. By identifying three primary approaches—cultural rehabilitation processes, the development of communication that values local culture, and conflict management skills—the study provides practical insights aligned with global efforts to improve mental health and social well-being in accordance with the SDG framework.